Simulation of the behavior of aluminum alloys welded in Friction Stir Welding FSW: (Case of AA5083 and AA 6082) (Fracture and Structural Integrity, 2018)
The friction stir welding FSW is a topical technique to date, either for experimental or numerical research topics. Based on the fact that the majority of the heat generated, comes from the contact between the workpiece and the shoulder, and from the work of friction done by the pin. Thus, it is crucial to approach the reality, by simulating the most of the conditions, related to the FSW process. The development of a numerical model allows us, not only to simulate the FSW welding process, but also to conduct a parametric study and vary the welding conditions as desired.Therefore, a numerical study is conducted on the friction stir welding of AA 5083H111 work piece, in order to perceive the optimal settings. A three dimensional model designed by ANSYS APDL was used.Before proceeding with this, a preliminary experimental study was carried out on FSW welded AA 6082 –T6 specimens and base material, using tensile and fatigue tests. The numerical results obtained, essentially longitudinal residual stresses, are compared to other studies, experimental and numerical.
Keywords: FSW; Parametric Study; AA5083H111; AA 6082-T6; Fatigue test